Existence and Hyers-Ulam Stability Results for Partial Fractional-Order Delay Differential Equations - Duman, Okan; Develi, Faruk (SPRINGER BASEL AG, 2022)
In this paper, we first give sufficient conditions for the existence and uniqueness results of the Darboux problem with delays for some partial fractional-order derivations in the sense of Caputo. Secondly, we prove a result regarding the Hyers-Ulam stability of this problem.
Keywords: Hyers-Ulam stability; fractional order derivative; Darboux problem; delay differential equations; INTEGRAL-EQUATIONS; UNIQUENESS; Mathematics